Bandhula sutesana - Kyoʻ Lvaṅʻ, Nhacʻ phakʻ lha Ūʺ (Haṃsāvatī Cā ʼupʻ Tuikʻ : ʼA praññʻ praññʻ chuiṅʻ rā Dhammagīri Vipassanā ʼA phvaiʹ mha phranʻʹ khyi pā saññʻ, 1993)
Research notes on Mahā Bandhula, 1782-1825, general of the Burmese army.